A rare Occurrence of Anonychia in a Neonate : A case Report - Mishra, Deepak; Ray, Pankaj; Jha, Chandra Bhal; Mishra, Rakesh (Medical Journal of Shree Birendra Hospital, 2023)
Congenital anonychia in isolated form is a rare anomaly in which there is an absence of nails of fingers and toes since birth. However, other ectodermal and mesodermal defects in the body are absent. Here, we report a case of 30-hour old female with e rare congenital disorder anonychia in fingernails of her left hand and all toenails. All other systemic examinations were normal. The baby was born of a consanguineous marriage, and the father also had absent nails in multiple fingers.